Moderasi Beragama dalam Pandangan Islam Ditinjau dari Kejelasan Nash Al-Quran dan Hadis - Harahap, Salahuddin; Thorieq Al Abdu; Andre Selamat Sinaga; Fikri Dwi Septian; Reyza Dian Isnaini; Muhammad Albani; Alwi Hadad; Mhd Wildan Arifin Baturara; Wahyu Septiawan; Mara Ganti Nasution; Muhammad Farhan Ramadhan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Moderation, or wasatiyyah, is an important principle taught in Islam, prioritizing balance and justice in worship and social interaction. This study uses a qualitative approach with a literature study method as the basis for analysis. In this context, data is collected from a variety of sources, including Qur'án nash, hadith, as well as relevant academic literature. Through the analysis of Qur'án texts and hadiths, this article identifies the values that support a moderate attitude, including the importance of tolerance, understanding, and justice. This research also examines the practical application of the principle of moderation in the context of the daily life of Muslims, as well as the challenges faced in promoting these values in the midst of the times. The results of this study are expected to provide deeper insights into the relevance of moderation in strengthening community solidarity and preventing extremism.